Creation of Social Value by Amazon Entrepreneurs - Zevallos Castañeda, María Mercedes (2023)
Social entrepreneurship is a concept often associated with ventures to develop products or services for national or international markets and the social benefits they generate. However, little is known about the impact of social entrepreneurship on indigenous communities such as those found in the Peruvian Amazon. This paper examines social value creation following the implementation of an educational process based on the development of entrepreneurship skills in leaders of multiethnic communities in Loreto, Peru. A quasi-experimental design was used to establish a comparison between an experimental group and a control group. It was found that the leaders of the intervention group outperformed the control group in terms of the promotion of collective learning, a higher level of association and a greater capacity to interact with institutions that support community development.